2014
DOI: 10.4314/tjpr.v13i5.7
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Mechanism of Antagonist Peptide for CC Chemokine Receptor 1 (CCR1) Derived from Viral Macrophage Inflammatory Protein II

Abstract: 25 and 13.1 ng/ml, respectively), and intracellular calcium mobilization. Conclusion:These results demonstrate that bioinformatics and protease digestion are feasible to screen and prepare C18P, and that C18P is a novel and specific small molecule peptide antagonist of CCR1 with therapeutic potential for preventing cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…It has been proven that vMIP-II has antagonistic activity against CCR1, CCR2B, CCR5, CCR8, CXCR3, and CXCR4, but not against CXCR1 or CXCR2. Its effect on CCR7 has not been clearly reported [6][7][8][9][10][11] . We previously found that vMIP-II competitively inhibits the binding of HIV to the co-receptors CCR5, CXCR4, and CCR3, among others, and used vMIP-II to prevent the virus from entering target cells and to study its role in resisting HIV infection 12,13 .…”
Section: Introductionmentioning
confidence: 98%
“…It has been proven that vMIP-II has antagonistic activity against CCR1, CCR2B, CCR5, CCR8, CXCR3, and CXCR4, but not against CXCR1 or CXCR2. Its effect on CCR7 has not been clearly reported [6][7][8][9][10][11] . We previously found that vMIP-II competitively inhibits the binding of HIV to the co-receptors CCR5, CXCR4, and CCR3, among others, and used vMIP-II to prevent the virus from entering target cells and to study its role in resisting HIV infection 12,13 .…”
Section: Introductionmentioning
confidence: 98%